ORGANIC WASTE'S POTENTIAL AS RENEWABLE ENERGY AT SUPIT URANG LANDFILL IN MALANG CITY - Saadiah, Riza; Hermawan, Hermawan; Hadiyanto, Hadiyanto (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2015)
This research are to know the correlation of the number of population with the amount of waste inMalang city and biogas potential at Supit Urang landfill. Then also counting the percentage of biogaswhich has been used as gas fuel by citizens around the landfill and as electrical energy potency. Theaverage amount of waste in Malang city is 410,45 ton per day. Organic waste composition at SupitUrang landfill is 64,9% or in the average it’s about 137.989,57 kg per day. From that amount, theaverage of biogas which is produced is 19.146,57 m3 per day or about 574.397,05 m3 per month.Biogas utilization is for fuel gas by 408 houses near the location of that landfill, that’s about 18.385,19m3 per month or about 3,2%. Therefore that’s still has 96,8% biogas potential or about 556.011,86 m3per month which has not been utilized yet. That potency can produce electrical energy 2.613.255,75kWh per month or 3,63 MW. If the average efficiency level of conversion from biogas to electricity is35%, the electric potential become 914.639,51 kWh per month or as big as power station with energy1,27 MW